Propofol has delayed myocardial protective effects after a regional ischemia/reperfusion injury in an in vivo rat heart model - Il Woo Shin; In Seok Jang; Seung-Hwa Lee; Ji-Seok Baik; Kyeong-Eon Park; Ju-Tae Sohn; Heon Keun Lee; Young Kyun Chung (Korean Journal of Anesthesiology, 2010)
BackgroundIt is well known that propofol protects myocardium against myocardial ischemia/reperfusion injury in the rat heart model. The aim of this study was to investigate whether propofol provides a protective effect against a regional myocardial ischemia/reperfusion injury in an in vivo rat heart model after 48 h of reperfusion.MethodsRats were subjected to 25 min of left coronary artery occlusion followed by 48 h of reperfusion. The sham group received profopol without ischemic injury. The control group received normal saline with ischemia/reperfusion injury. The propofol group received profopol with ischemia/reperfusion injury. The intralipid group received intralipid with ischemia/reperfusion injury. A microcatheter was advanced into the left ventricle and the hemodynamic function was evaluated. The infarct size was determined by triphenyltetrazolium staining. The serum level of cardiac troponin-I (cTn-I) was determined by ELISA (enzyme-linked immunosorbent assay).ResultsPropofol demonstrated protective effects on hemodynamic function and infarct size reduction. In the propofol group, the +dP/dtmax (P = 0.002) was significantly improved compared to the control group. The infarct size was 49.8% of the area at risk in the control group, and was reduced markedly by administration of propofol to 32.6% in the propofol group (P = 0.014). The ischemia/reperfusion-induced serum level of cTn-I was reduced by propofol infusion during the peri-ischemic period (P = 0.0001).ConclusionsPropofol, which infused at clinically relevant concentration during the peri-ischemic period, has delayed myocardial protective effect after regional myocardial ischemia/reperfusion injury in an in vivo rat heart model after 48 h of reperfusion.